Lighting the local area optical code-division multiple access and quality of service provisioning. - Stok, A.
Asynchronous, high-speed multiple-access is proposed as a natural solution to achieving asynchronous, high-speed connectivity in a local area network environment. Optical CDMA is shown to be competitive with other networking technologies such as WDMA and TDMA, but has the benefit of more flexibility, simpler protocols, and no need for centralized network control. The limitations of one-dimensional optical orthogonal codes for CDMA have motivated the idea of spectral spreading in both the temporal and wavelength domains. If the constraints on constant weight in these two-dimensional codes are relaxed, differentiated levels of service at the physical layer become possible. Areas for further research are suggested which may allow quality of service levels to be guaranteed at the physical layer.
Keywords: LAN; QoS provisioning; TDMA; WDMA; Asynchronous high-speed multiple-access.; Constant weight constraints; High-speed connectivity; Local area network; Networking technologies; One-dimensional optical orthogonal codes; Optical CDMA; Optical code-division multiple access; Physical layer; Protocols; Quality of service provisioning; Spectral spreading; Temporal domain; Two-dimensional codes; Wavelength domain